(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The ecological state of several flooded quarries in the Kaliningrad Region was studied: Yantarny, the largest in area, formed as a result of filling the basin of a former amber quarry, as well as Berezovsky and Pushkarevsky, which were previously used for sand and gravel extraction. The results of hydrochemical studies showed that all the studied water bodies are in a good ecological state, but water quality in the Yantarny quarry is in a better ecological condition. According to zooplankton indicators, the water quality in all the studied quarries is assessed similarly, but in the Yantarny quarry, lower values of trophicity, trophic index and saprobity coefficients of water are noted, which also indicates better water quality in it.